Core competencies for ethics experts in health technology assessment. (9th December 2020) - Refolo, Pietro; Bond, Kenneth; Bloemen, Bart; Autti-Rämö, Ilona; Hofmann, Bjørn; Mischke, Claudia; Mueller, Debjani; Nabukenya, Sylvia; Oortwijn, Wija; Sandman, Lars; Stanak, Michal; Steele, Duncan; et al.
Abstract: Objectives: There is no consensus on who might be qualified to conduct ethical analysis in the field of health technology assessment (HTA). Is there a specific expertise or skill set for doing this work? The aim of this article is to (i) clarify the concept of ethics expertise and, based on this, (ii) describe and specify the characteristics of ethics expertise in HTA. Methods: Based on the current literature and experiences in conducting ethical analysis in HTA, a group of members of the Health Technology Assessment International (HTAi) Interest Group on Ethical Issues in HTA critically analyzed the collected information during two face-to-face workshops. On the basis of the analysis, working definitions of "ethics expertise" and "core competencies" of ethics experts in HTA were developed. This paper reports the output of the workshop and subsequent revisions and discussions online among the authors. Results: Expertise in a domain consists of both explicit and tacit knowledge and is acquired by formal training and social learning. There is a ubiquitous ethical expertise shared by most people in society; nevertheless, some people acquire specialist ethical expertise. To become an ethics expert in the field of HTA, one needs to acquire general knowledge about ethical issues as well as specific knowledge of the ethical domain in HTA. The core competencies of ethics experts in HTA consist of three fundamental elements: knowledge, skills, and attitudes. Conclusions: The competencies described here can be used by HTA agencies and others involved in HTA to call attention to and strengthen ethical analysis in HTA.